PERANCANGAN SISTEM INFORMASI SIMPAN PINJAM DI KOPERASI BINA MASYARAKAT TARATAK KOTO LUA KECAMATAN PAUH PADANG BERBASIS JAVA - Elmawati Elmawati (Universitas Negeri Padang, 2018)
The Designation of Save Loan Information System in Cooperative Community Development Koto Lua District Pauh Padang database to be more easier in processing save-loan cooperation data. This system can process member data, saving and loan. Then, in data processing it can process faster than usual so it is raised a report and information of save-loan cooperation that are suitable with members. Necessity data processing is done by the administration Cooperative Community Development Koto Lua District Pauh Padang agreed by leader and treasurer